PENGELOMPOKAN DAERAH DI KOTA MALANG BERDASARKAN POTENSI WILAYAH DAN SARANA-PRASARANA PENUNJANG SOSIAL-EKONOMI SEBAGAI DASAR PERUMUSAN KEBIJAKAN - Eva Fadilah Ramadhani (Bappeda Kota Malang, 2023)
The study aimed to group sub-districts in Malang City based on regional potential and socio-economic supporting infrastructure using the cluster analysis method with the Ward method and single linkage. The data used in this study were obtained from the Central Bureau of Statistics publication in 2022. In this study, 12 variables were used to describe the potential and infrastructure available in Malang. The grouping results show that there are two clusters. Cluster 1 consists of Kedungkandang and Sukun sub-districts, while cluster 2 consists of Klojen, Blimbing, and Lowokwaru sub-districts. Cluster 1 is superior in area, population, horticulture production, livestock production, plantation production, and the number of elementary schools. While cluster 2 excels in fishery production, number of junior and senior high schools, number of health facilities, cooperatives, and hotels. The originality of this research is the use of the cluster analysis method with the Ward method and single linkage in classifying regions based on regional potential and socio-economic supporting infrastructure in Malang City. The grouping results can be used to formulate policies to utilize the region's potential and the socio-economic supporting infrastructure in each cluster.